United Nations Declaration and International Convention on the Elimination of All Forms of Racial Discrimination (United Nations Departmnet of Public Information [New York]US, 1997)
Contains the full texts of the Declaration and the Convention; the list of States parties to the Convention; a description of the work of the Committee on the Elimination of Racial Discrimination; and, a brief chronology of related efforts by the United Nations to combat racism.
DC